Physical Activity Development Model Using Traditional Balinese Game in Junior High School - Hendry Wijaya Kusuma; Moch. Asmawi; Hernawan Hernawan; Firmansyah Dlis; I Nyoman Kanca (PendIPA Journal of Science Education, 2020)
This study aims to develop learning of physical activity using traditional Ballinese in junior high schools, Buleleng Regency. Students can learn physical materials without feeling bored and tired. This study refer to research and development model by Borg and Gall. From the research and development, as well as the proposed procedures, the resulting product is a physical fitness learning model based on traditional Balinese games in junior high schools that consist of 30 traditional Balinese games. Product development begun with expert studies, field tests in small and large test groups and. Effectiveness tests. From the large-group test results, the model developed can be applied by students properly. In the effectiveness test, the mean of the control group was 364.08, while the mean of the experimental group was 350.00 that show the difference between the results of the experimental group and the control group. It can be concluded that there is a significant difference between the experimental group given the treatment and the control group. Product development can be ,improved significantly on the physical activity and attitude or affective student. Based on the results of the research, the product model of learning physical fitness activities based on traditional Balinese games can be recommended and can be effective as a learning model of physical fitness activities in junior high schools.